VD_FINDINFO HC / 2013 / 151 vom 5. März 2013 - VD Tribunal cantonal (2013)
BAIL À LOYER, RÉSILIATION, ABUS DE DROIT, TERME COMMINATOIRE, EXPULSION DE LOCATAIRE, LOYER, PAIEMENT DE L'ARRIÉRÉ | 257d CO, 257 CPC (CH)